2019
DOI: 10.1055/s-0038-1677018
|View full text |Cite
|
Sign up to set email alerts
|

How to Optimize Activated Partial Thromboplastin Time (APTT) Testing: Solutions to Establishing and Verifying Normal Reference Intervals and Assessing APTT Reagents for Sensitivity to Heparin, Lupus Anticoagulant, and Clotting Factors

Abstract: The activated partial thromboplastin time (APTT) assay is a very common coagulation test, used for several reasons. The test is conventionally used for assessing the contact factor (intrinsic) pathway of blood coagulation, and thus for screening deficiencies in this pathway, most typically factors VIII, IX, and XI. The APTT is also sensitive to contact factor deficiencies, including factor XII, prekallikrein, and high-molecular-weight kininogen. The APTT may also be elevated in a variety of conditions, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Additionally, variations in reagents and laboratory specificities are more pronounced with aPTT [ 22 ]. Indeed, unlike PT which is normalised between centres using the International Normalised Ratio, each laboratory must set up a specific heparin therapeutic range, resulting in serious discordance between centres [ 23 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, variations in reagents and laboratory specificities are more pronounced with aPTT [ 22 ]. Indeed, unlike PT which is normalised between centres using the International Normalised Ratio, each laboratory must set up a specific heparin therapeutic range, resulting in serious discordance between centres [ 23 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic pathway may be monitored using aPTT. Severe to moderate deficiencies of important intrinsic pathway coagulation factors such as II, V, VIII, IX and XI can be detected and usually present with a prolonged aPTT, whereas mild factor deficiencies often remain unnoticed [24,25].…”
Section: Activated Partial Thromboplastin Time (Aptt) Prothrombin Time (Pt) and International Normalised Ratio (Inr)mentioning
confidence: 99%
“…aPTT monitoring requires internal laboratory standardization, as numerous variables impact the result, including elevated levels of fibrinogen that result from acute phase reactions. 72 , 73 The standard therapeutic range, defined as 1.5–2.5 greater than the upper limit of normal, is mainly derived from older studies, 74 and a more recent study including a heterogeneous population suggested that this range could potentially lead to inappropriate UFH dosing. 75 An analysis of the OASIS study population found lower limit of the therapeutic range of 60 s to be associated with the lowest risk for recurrent ischaemic events.…”
Section: Cardiogenic Shock In Settings Of Acute Coronary Syndromementioning
confidence: 99%